The Effect of Continuous Care Model on Quality of Life of women with Endometriosis: A Quasi -Experimental Study - fatemeh jalalinezhad; khadijeh shadjoo; roghieh bayrami; vahid alinezhad (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: The relatively high prevalence of endometriosis in women of childbearing age and its negative impact on the health related quality of life, requires the use of intervention appropriate to their conditions. The aim of present study was determining the effect of using the continuous care model on the quality of life of women with endometriosis. Materials and Methods: This non-parallel semi-experimental study was conducted from December 2022 to September 2023 on 60 people (30 people in each group) of women with endometriosis with convenience sampling at Avicenna Clinic in Tehran. For the intervention group, the continuous care model was implemented in four stages among three months. The 30-EHP quality of life questionnaire was completed before, two and three months after the end of the intervention. Data were analyzed using chi-square tests, independent t- test and repeated measures analysis of variance in SPSS16 software. Results: The mean scores of pain, degree of control, emotional, social support, self-perception, job, intercourse, efficiency of existing treatments and perception of infertility dimensions were statistically significant in measurements before, two months and three months after the intervention in two groups(P<0.05). However, no statistically significant difference was observed regarding the dimensions of relationship with the child (P=0.085) and medical attention (P=0.271). Conclusion: The continuous care model has improved some aspects of the quality of life, except for the aspects of the relationship with the child and medical attention. It is suggested to use other interventions to improve these aspects along with continues care model.